Single-Walled (Magnetic) Carbon Nanotubes in a Pectin Matrix in the Design of an Allantoin Delivery System - BATIREL, SAİME; ŞAHİN, ALİ (My University, 2023)
Single-walled carbon nanotubes (SWCNTs) outperform other materials due to their high conductivity, large specific surface area, and chemical resistance. They have numerous biomedical applications, including the magnetization of the SWCNT (mSWCNT). The drug loading and release properties of see-through pectin hydrogels doped with SWCNTs and mSWCNTs were evaluated in this study. The active molecule in the hydrogel structure is allantoin, and calcium chloride serves as a cross-linker. In addition to mixing, absorption, and swelling techniques, drug loading into carbon nanotubes was also been studied. To characterize the films, differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, surface contact angle measurements, and opacity analysis were carried out. Apart from these, a rheological analysis was also carried out to examine the flow properties of the hydrogels. The study was also expanded to include N-(9-fluorenyl methoxycarbonyl)glycine-coated SWCNTs and mSWCNTs as additives to evaluate the efficiency of the drug-loading approach. Although the CNT additive was used at a 1:1000 weight ratio, it had a significant impact on the hydrogel properties. This effect, which was first observed in the thermal properties, was confirmed in rheological analyses by increasing solution viscosity. Additionally, rheological analysis and drug release profiles show that the type of additive causes a change in the matrix structure. According to TGA findings, even though SWCNTs and mSWCNTs were not coated more than 5%, the coating had a significant effect on drug release control. In addition to all findings, cell viability tests revealed that hydrogels with various additives could be used for visual wound monitoring, hyperthermia treatment, and allantoin release in wound treatment applications.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, CHEMICAL; Genel Kimya; Fizik Bilimleri; Genel Kimya Mühendisliği; General Chemistry; Physical Sciences; General Chemical Engineering